Dampak Perkembangan Digital Terhadap Penggunaan Bahasa Indonesia dalam Pendidikan Inklusif - Rosita; Nur’Asmi (PT. Saha Kreasi Indonesia, 2025)
The development of digital technology has had a significant impact on the use of Indonesian in the context of inclusive education. Through a literature review of national journals published between 2023 and 2025, this article examines how digital media affects accessibility, language quality, and the Indonesian language learning process for students with special needs. The study results indicate that digital developments have had a positive impact in the form of increased access to materials, multimodal support, and strengthened learning motivation. Digital media allows for the presentation of materials in audio, visual, and interactive formats, thus facilitating understanding for students with visual impairments, hearing impairments, and students with different learning styles. However, digitalization has also given rise to problems such as a decline in the use of formal language, an increase in digital abbreviations, code-mixing, and a weakening of formal writing skills. Furthermore, challenges arise in the form of a digital literacy gap among teachers and students. Overall, digitalization presents significant opportunities for the development of Indonesian language learning in inclusive education, but digital literacy strategies and strengthened language policies are needed to ensure language use remains sustainable and relevant for all students.